2020
DOI: 10.1186/s12913-019-4774-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the implementation of a community-based hypertension improvement project in Ghana: a qualitative study of ComHIP

Abstract: Background: Globally, hypertension is a leading cause of cardiovascular disease and mortality, with the majority of deaths occurring in low-and middle-income countries. Because the burden of hypertension is increasing in low resource settings with restricted infrastructure, it is imperative that new models for hypertension care are realised. One such model is the Community-based Hypertension Improvement Project (ComHIP) which employs a community-based method of task-shifting for managing hypertension. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Table 4 summarises the number of studies relevant to each of the seven levels of community participation across the four phases of project development. The highest levels of participation (level 5 to level 7) were found in the diagnosis phase for two studies (13.3%) [ 30 , 31 ], in the development phase for four studies (26.7%) [ 8 , 29 , 30 , 32 ] in the implementation phase for five studies (33.3%) [ 8 , 29 , 30 , 32 , 33 ] and in the evaluation phase for three studies (17.6%) [ 31–33 ]. Overall, levels of participation were highest in one of the studies on healthcare quality, although evaluation was scored as ‘unknown’ [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 summarises the number of studies relevant to each of the seven levels of community participation across the four phases of project development. The highest levels of participation (level 5 to level 7) were found in the diagnosis phase for two studies (13.3%) [ 30 , 31 ], in the development phase for four studies (26.7%) [ 8 , 29 , 30 , 32 ] in the implementation phase for five studies (33.3%) [ 8 , 29 , 30 , 32 , 33 ] and in the evaluation phase for three studies (17.6%) [ 31–33 ]. Overall, levels of participation were highest in one of the studies on healthcare quality, although evaluation was scored as ‘unknown’ [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The participation of the community was described with insufficient detail to be assessed (unknown category) for one study in the Development phase (5.8%) [ 33 ] and one (5.8%) in the Evaluation phase [ 30 ]. Overall, levels of community participation across all studies were assessed as low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Similarly, community-based hypertension screening and treatment activities in Ghana also encountered problems, one of which was the availability of facilities and infrastructure. 23 The basic examinations expected to be performed at the PHCs included blood pressure, height, weight, waist circumference, and hip circumference measurements. These measurements required simple tools.…”
Section: The Availability Of Facilities and Infrastructure For Hypert...mentioning
confidence: 99%
“…A study in Ghana found that health workers thought the activities conducted outside of working hours should be balanced with appropriate compensation. 23 Other recommendation is to provide service at two times schemes, morning for elderly or non-working target and evening for younger groups.…”
Section: Community Participation In Hypertension Screening Activitiesmentioning
confidence: 99%